A history of the book in America. Volume 5, The enduring book, print culture in postwar America - Nord, David Paul; Rubin, Joan Shelley, 1947-; Schudson, Michael; American Antiquarian Society (Chapel Hill : Published in association with the American Antiquarian Society by the University of North Carolina Press, 2009)
V. 1. The colonial book in the Atlantic world: This book carries the interrelated stories of publishing, writing, and reading from the beginning of the colonial period in America up to 1790. v. 2 An Extensive Republic: This volume documents the development of a distinctive culture of print in the new American republic. v. 3. The industrial book 1840-1880: This volume covers the creation, distribution, and uses of print and books in the mid-nineteenth century, when a truly national book trade emerged. v. 4. Print in Motion: In a period characterized by expanding markets, national consolidation, and social upheaval, print culture picked up momentum as the nineteenth century turned into the twentieth. v. 5. The Enduring Book: This volume addresses the economic, social, and cultural shifts affecting print culture from Word War II to the present.
v. 1. The colonial book in the Atlantic world -- v. 2. An extensive republic: print, culture, and society in the new nation, 1790-1840 -- v. 3. The industrial book, 1840-1880 -- v. 4. Print in motion: the expansion of publishing and reading in the United States, 1880-1940 -- v. 5. The enduring book: print culture in postwar America.
Includes bibliographical references and indexes.
Print version record.
English.
JSTOR
Keywords: Book industries and trade -- United States -- History -- 17th century; Book industries and trade -- United States -- History -- 18th century; Publishers and publishing -- United States -- History -- 17th century; Publishers and publishing -- United States -- History -- 18th century; Publishers and publishing -- United States -- History -- 19th century; Publishers and publishing -- United States -- History -- 20th century; Livres -- Industrie -- États-Unis -- Histoire -- 17e siècle.; Livres -- Industrie -- États-Unis -- Histoire -- 18e siècle.; BUSINESS & ECONOMICS -- Commerce; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Sales & Selling -- General; HISTORY -- United States -- 20th Century; Book industries and trade; Publishers and publishing; United States; 1600-1999; History